RESISTENSI MASYARAKAT TERHADAP ELITE BARU PASCA-HELSINKI DI ACEH - Iromi Ilham (Department of Anthropology, 2018)
The reconcilement of Helsinki became the gateway of the Acehnese transformation which has implicated to the social and political change in Aceh. One other thing is the emergence of former GAM fighter as the new Acehnese elite. The collective trauma of the Aceh community led by